Leadership and Multicultural Environment; Kyai's Power and Authority Contest at Pondok Pesantren - Rahman, Kholilur (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
This paper aims to understand spiritual leadership from the personal point of view, power, and authority. The central concept of leadership in this landscape is how a leader can impact people who have different attitudes, motivations, origins, personality values, beliefs, and of course, culture from a sociological-anthropological perspective. In addition to looking at aspects of multicultural leadership, the author will also enrich this study by studying a character, namely KH Muwafiq Amir. A Kyai who has power and authority in the Pondok Pesantren Bustanul Makmur, Genteng, Banyuwangi. An influence that will be read through the paradigm of power and authority. This study uses a qualitative method with a phenomenological approach. The results showed that KH Muwafiq Amir was 'appointed' as chairman of the Board of Caregivers in this pesantren environment outside the customs or traditions different from pesantren in general; where the succession of leadership is determined by lineage. Meanwhile, KH Muwafiq Amir is not a direct descendant (read; biological) from the Big Family of the Pondok Pesantren Bustanul Makmur.